Keloid Co-Existing with epidermoid Cyst in a Black Elderly Patient: A Case Report - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Keloid is an abnormal scar that can be due to tissue trauma or occur spontaneously. It commonly occurs in dark pigmented individuals with positive family history. Epidermoid cyst (EC) on the other hand is an adnexal cysts that contain keratin and stratified epithelium. The co-existence of both keloid and EC is rare and very few have been reported in the literature especially among the Negroids. The objective is to report a keloid mass co-existing with an EC in a Negroid elderly patient. A 76-year-old man presented with right sided upper back swelling of a year duration with no prior trauma or family history of keloid. Physical examination showed a 2 × 7 cm raised keloid scar with an intraoperative incidental finding of a 1 × 1 cm hemispheric epidermoidcyst. The significance of this case is in the rarity of co-existing keloid and EC especially in the elderly and Negroids.